Self-Esteem as a Moderator of the Influence of Peer Pressure on Adolescent Aggression - A.N. Wulandari; N. Ni’matuzahroh; I. Istiqomah (Психолого-педагогические исследования)
This study aims to investigate the effect of peer pressure on adolescent aggression with self-esteem as a moderator. Data in this regression quantitative study were collected through online self-report using questionnaires from junior high school adolescents (N=348) whose ages ranged from 12-15 years old. Data were analyzed using Moderated Regression Analysis (MRA). The research subjects completed the research instrument, namely the Buss-Perry Aggression Questionnaire Scale (BPAQ), Peer Pressure Inventory (PPI), and Rosenberg Self-Esteem Scale (RSES). The results showed that peer pressure had a significant positive effect on adolescent aggression, but self-esteem did not serve as a moderator in the relationship. The findings showed that the more often adolescents received peer pressure, the higher the level of involvement in the aggressive behavior of their peer group. However, self-esteem could not to weaken or strengthen the effect of peer pressure on adolescent aggression.